DIAGNOSIS DAN TATA LAKSANA KEKAMBUHAN KUSTA - Caroline Oktarina; Melani Marissa; Wresti Indriatmi; Sri Linuwih Menaldi (Perhimpunan Dokter Spesialis Kulit dan Kelamin Indonesia (PERDOSKI), 2022)
Leprosy relapse is defined as the reappearance of leprosy’s signs and symptoms following completion of adequate Multidrug Therapy (MDT) regimen. Indonesia is the third biggest contributor for leprosy relapse with 284 cases in 2018. Several factors contribute to the occurrence of relapse, which include presence of persisters, history of inadequate therapy, drug resistance, history of irregular treatment, history of dapsone monotherapy, high initial bacteriological index, high number of skin and nerve lesions, negative lepromin test, history of antireaction therapy, human immunodeficiency virus (HIV) infection, and pregnancy. Diagnosis of relapse can be established based on clinical, bacteriological, and therapeutic criteria, also histopathological and serological criteria, if possible. With those criteria, it should be easier to differentiate relapse from reaction, resistance, reactivation, and reinfection. The principal management for leprosy relapse is re-administration of MDT according to the type of relapse; however, therapy should be modified if there are any evidences of drug resistance. Things which are important to be taken into account during relapse treatment are leprosy type, past medication history, and the possibility of drug resistance. With proper knowledge and diagnostic algorithm, it is expected that the treatment can be administered immediately in order to prevent disability and transmission of infection.